Evaluasi Sistem Drainase Kelurahan Sudajaya Hilir, Kecamatan Baros, Kota Sukabumi - Eka Wardhani; Bagya Trirahmani, Anggia (Jurnal Serambi Engineering, 2025)
Sudajaya Hilir Village, Baros District, Sukabumi City, is one of the areas prone to flooding due to drainage capacity and land use changes. This study aims to evaluate the condition of existing channels and analyze their capacity using the EPA Storm Water Management Model (SWMM). The data used includes field surveys on the dimensions and condition of the channels, historical rainfall data, and drainage planning documents from the Sukabumi City Public Works and Spatial Planning Agency. The evaluation results show that the dimensions of the existing channels are not in accordance with the plan. The SWMM simulation identified points 1 to 5 along Jalan Lingkar Selatan. The difference in size between points 1 and 5 ranged from 0.05 to 0.20 meters. The SWMM simulation identified points 4 and 5 as having low elevations. Based on the simulation results, recalculations were performed to reduce the potential for flooding in the area. The recommended measure is to increase the width of the drainage channel at points 1 to the outfall by 0.1 to 0.4 meters. In addition, the construction of a retention pond at locations with lower elevations is also recommended to accommodate excess water discharge. With a combination of channel dimension improvements and the provision of retention ponds, the capacity of the drainage system is expected to increase, thereby reducing the risk of flooding more effectively.